Two Beats One: Osteosarcoma Therapy with Light-Activated and Chemo-Releasing Keratin Nanoformulation in a Preclinical Mouse Model - Elisa Martella; Barbara Dozza; Claudia Ferroni; Clement Osuru Obeyok; Andrea Guerrini; Daniele Tedesco; Ilse Manet; Giovanna Sotgiu; Marta Columbaro; Marco Ballestri; Lucia Martini; Milena Fini; et al. (MDPI AG, 2022)
Osteosarcoma treatment is moving towards more effective combination therapies. Nevertheless, these approaches present distinctive challenges that can complicate the clinical translation, such as increased toxicity and multi-drug resistance. Drug co-encapsulation within a nanoparticle formulation can overcome these challenges and improve the therapeutic index. We previously synthetized keratin nanoparticles functionalized with Chlorin-e6 (Ce6) and paclitaxel (PTX) to combine photo (PDT) and chemotherapy (PTX) regimens, and the inhibition of osteosarcoma cells growth in vitro was demonstrated. In the current study, we generated an orthotopic osteosarcoma murine model for the preclinical evaluation of our combination therapy. To achieve maximum reproducibility, we systematically established key parameters, such as the number of cells to generate the tumor, the nanoparticles dose, the design of the light-delivery device, the treatment schedule, and the irradiation settings. A 60% engrafting rate was obtained using 10 million OS cells inoculated intratibial, with the tumor model recapitulating the histological hallmarks of the human counterpart. By scheduling the treatment as two cycles of injections, a 32% tumor reduction was obtained with PTX mono-therapy and a 78% reduction with the combined PTX-PDT therapy. Our findings provide the in vivo proof of concept for the subsequent clinical development of a combination therapy to fight osteosarcoma.